2014
DOI: 10.3109/10717544.2014.975382
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-loaded nanostructured lipid carriers (NLCs) for nasal administration: design, characterization, and in vivo study

Abstract: Cancer nanotherapeutics is beginning to overwhelm the global research and viewed to be the revolutionary treatment regime in the medical field. This investigation describes the development of a stable nanostructured lipid carrier (NLC) system as a carrier for curcumin (CRM). The CRM-loaded NLC developed as a particle with the size of 146.8 nm, a polydispersity index of 0.18, an entrapment efficiency (EE) of 90.86%, and the zeta potential (ZP) of À21.4 mV. Besides, the increased cytotoxicity of CRM-NLC than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(101 citation statements)
references
References 23 publications
2
98
0
1
Order By: Relevance
“…Testing in Wistar rats showed that maximum concentration was reached after approximately 3 hours, and delivery to brain tissues was greater with the lipid carrier than the plain drug suspension (86 and 54 ng/g, resp.) [79]. …”
Section: Delivery Mechanismsmentioning
confidence: 99%
“…Testing in Wistar rats showed that maximum concentration was reached after approximately 3 hours, and delivery to brain tissues was greater with the lipid carrier than the plain drug suspension (86 and 54 ng/g, resp.) [79]. …”
Section: Delivery Mechanismsmentioning
confidence: 99%
“…Nanostructured lipid carriers (NLCs), the latest generation of lipid-based nanoparticles, were introduced in the late 1990s. NLCs were composed of a binary mixture of a solid lipid and a liquid lipid (Madane & Mahajan, 2014). Given their structure and characteristics, NLCs can be considered as preferable nanovectors to load poor soluble drugs; increase drug loading and longer assure molecule stability (Shidhaye et al, 2008;Han et al, 2015;Shao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There are many nanodelivery systems reported in recent years, including PLGA (Mayol et al, 2015), polymer (1) denotes lower concentration of 10 mg/mL, (2) denotes higher concentration of 20 mg/mL, and doses are based on the amount of CUR. (Alizadeh et al, 2015), SLNs and NLCs (Madane & Mahajan, 2014). Both SLNs and NLCs are reported as an ideal nanocarrier for helping passing through the BBB, and NLC appears to be superior to SLN with smaller particle size and higher drug loading (Gokce et al, 2012).…”
Section: Discussionmentioning
confidence: 99%